PENANAMAN NILAI KARAKTER NASIONALISME DAN PATRIOTISME PADA PEMBELAJARAN TEMATIK BERMUATAN IPS SISWA KELAS IV SD NEGERI SINGOSAREN BANTUL - Rahmatiya, Ita; Zulfiati, Heri Maria (Universitas Sarjanawiyata Tamansiswa, 2020)
This research aims to describe: (1) An overview of the value of the character of nationalism and patriotism that students have, (2) The implementation of the value of character planting nationalism and patriotism, (3) The inhibitory factor and solution carried out in the implementation of the value of character planting nationalism and patriotism on thematic learning with the IPS of grade IV students Elementary School state Singosaren Bantul. This research is qualitative descriptive research. Research data sources are principals, teacher classes, and students. Data collection techniques using observation techniques, interviews, and documentation. These research instruments are observation guidelines, interview guidelines, and documentation. Test the validity of data using an extension of observation, increase persistence, triangulation (source triangulation, technique, and timing), and use reference material. The data analysis techniques in this study used Miles and Huberman analyses consisting of data collection, data reduction, data presentation, and withdrawal conclusions. The results showed that (1) the idea of the value of nationalism and patriotism character is that students already have the value of nationalism and patriotism in themselves and also have been able to apply attitudes to the value of the character in everyday life even though not maximally. (2) The implementation of the character value of nationalism and patriotism in the learning of IPS-charged thematic, by inserting the value of the character in the learning materials, using the learning media, using inspirational stories and showing heroic films to motivate students, doing outing class activities in the museum, through school activities and policies such as performing flag ceremonies, singing national songs and local songs, using traditional clothing (3) Inhibitory factor and solution done in the implementation of the value of character planting nationalism and patriotism in the thematic learning with the IPS of grade IV students Elementary School state Singosaren Bantul namely a factor that comes from the self, factors of environmental condition of students who are less conducive, experiencing addiction in the use of gadgets, school facilities that have not been fully fulfilled in support of the to overcome this problem, the solution is to provide direct guidance to the students who have less interest during the process of learning IPS-charged thematic, doing a variety of activities that are performed as a means of meeting with the parents.